Structural Analysis of Love, Sacrifice, and Irony in The Gift of the Magi by O. Henry - Putri Setia L. Tobing; Jihan Khairunnisa; Selli Malika; Oktavia Rezeki Anggreni Silaen; Jennifer Yolanda Saragih; T. Thyrhaya Zein (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze love, sacrifice, and irony in O. Henry’s short story “The Gift of the Magi”. The study focuses on how intrinsic elements, such as characters, conflict, plot, and irony, are interrelated in constructing the story’s meaning. Additionally, this study aims to explain how the economic conflict in the story drives acts of sacrifice and produces situational irony that reinforces the representation of love and sincerity. This study employs a qualitative method with a descriptive approach. The primary data source is O. Henry’s short story The Gift of the Magi, while supplementary data comes from journals, books, and prior research relevant to structuralist theory and literary studie. Data collection was conducted through documentation and library research. Data analysis was performed using the steps outlined by Miles, Huberman, and Saldana. This study was also supported by Creswell’s analysis stages to strengthen data interpretation. The results of the study indicate that love serves as the primary driving force behind the sacrificial actions of both characters. Economic conflict functions as the main catalyst for the development of the plot, while situational irony at the story’s conclusion clarifies the meaning of the sincerity of love. This study found that the story’s meaning is constructed through structural relationships among intrinsic elements. Thus, the structuralist approach proves relevant for understanding how a story’s structure generates meaning comprehensively.